2022
DOI: 10.1136/bmjebm-2021-111859
|View full text |Cite
|
Sign up to set email alerts
|

Quality of reporting among systematic reviews underpinning the ESC/ACC guidelines on ventricular arrhythmias and sudden cardiac death

Abstract: ObjectivesThe main objective of this study was to assess the methodological and reporting quality of the systematic reviews (SRs) supporting the European Society of Cardiology (ESC) and the American College of Cardiology (ACC) clinical practice guidelines (CPGs) recommendations for the management of patients with ventricular arrhythmias and sudden cardiac death (SCD). As a secondary objective, we sought to determine: (1) the proportion of Cochrane SRs were cited; and (2) whether Cochrane SRs scored higher on P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated an association between patient outcomes and quality of CPGs (Berlin et al, 2015;Garrett et al, 2022). Thus, providing nurses with a synthesised set of recommendations from highly rated CPGs is the first step in ensuring quality of PSD nursing, irrespective of severity of dysphagia or medical locations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated an association between patient outcomes and quality of CPGs (Berlin et al, 2015;Garrett et al, 2022). Thus, providing nurses with a synthesised set of recommendations from highly rated CPGs is the first step in ensuring quality of PSD nursing, irrespective of severity of dysphagia or medical locations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated an association between patient outcomes and quality of CPGs. 30 31 Thus, providing nurses with a synthesised set of recommendations (from highly rated CPGs) is the first step in ensuring quality of PSD nursing, irrespective of severity of depression or medical locations. The results demonstrated differences between CPGs which could be expected to significantly impact nursing care of PSD.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic search of CPGs related to PSD was performed in this study. Previous studies have demonstrated an association between patient outcomes and quality of CPGs 30 31. Thus, providing nurses with a synthesised set of recommendations (from highly rated CPGs) is the first step in ensuring quality of PSD nursing, irrespective of severity of depression or medical locations.…”
Section: Discussionmentioning
confidence: 99%
“…When a crisis occurs, the decision-makers of enterprises often face untimely, incomplete or even inaccurate information, which leads to the damage of corporate image or product reputation. Sometimes a crisis is enough to make the long-term investment of enterprises go down the drain, and the image is destroyed or even withdrawn from the market [3][4].…”
Section: Frequent Corporate Crisesmentioning
confidence: 99%